Tailoring robot-assisted arm training to individuals with stroke: bridging neuroscience principles and clinical practice - Morone, Giovanni; Tramontano, Marco; Paolucci, Stefano; Cerasa, Antonio; Ciancarelli, Irene; Martino Cinnera, Alex; Iosa, Marco; Calabrò, Rocco Salvatore (Frontiers in Neurology, 2025)
Robot-assisted arm training (RAAT) has demonstrated promising potential in improving rehabilitation outcomes for individuals with neurological conditions, particularly stroke. Despite 20 years of their use in clinical and research settings, there are still significant needs to be made concerning clinical indications. In the present perspective manuscript, we provide some hypotheses of the suitability of different RAAT according to the features of the available devices and clinical characteristics, showing their limitations and strengths. Several factors were considered in the optimization of RAAT intervention, including the technological characteristics of the devices (e.g., support and constriction), the residual upper limb motor function, and the clinical phase of stroke. Finally, we outline key areas for improvement to advance the field in the near future and provide neuroscientific bases for hypotheses of tailored RAAT training to improve the outcome of robotic rehabilitation.